Wnt/β-Catenin and Hippo Pathway Deregulation in Mammary Tumors of Humans, Dogs, and Cats. Issue 6 (November 2020) - Sammarco, Alessandro; Gomiero, Chiara; Sacchetto, Roberta; Beffagna, Giorgia; Michieletto, Silvia; Orvieto, Enrico; Cavicchioli, Laura; Gelain, Maria Elena; Ferro, Silvia; Patruno, Marco; Zappulli, Valentina
Mammary cancer is a common neoplasm in women, dogs, and cats that still represents a therapeutic challenge. Wnt/β-catenin and Hippo pathways are involved in tumor progression, cell differentiation, and metastasis. The aim of this study was to evaluate mRNA and protein expression of molecules involved in these pathways in human (HBC), canine (CMT), and feline mammary tumors (FMT). Real-time quantitative polymerase chain reaction (qPCR) for β-catenin, CCND1, YAP, TAZ, CTGF, and ANKRD1, western blotting for YAP, TAZ, and β-catenin, and immunohistochemistry for estrogen receptor (ER), progesterone receptor (PR), ERBB2, β-catenin, and YAP/TAZ were performed on mammary tumor tissues. The protein expression of active β-catenin was higher in tumors than in healthy tissues in all 3 species. The mRNA expression of the downstream gene CCND1 was increased in HBC ER + and CMTs compared to healthy tissues. Membranous and cytoplasmic protein expression of β-catenin were strongly negatively correlated in all 3 species. Tumors showed an increased protein expression of YAP/TAZ when compared to healthy tissues. Notably, YAP/TAZ expression was higher in triple negative breast cancers when compared to HBC ER + and in FMTs when compared to CMTs. The mRNA expression of β-catenin, YAP, TAZ, CTGF, and ANKRD1 was not different between tumors and healthy mammary gland in the 3 species. This study demonstrates deregulation of Wnt/β-catenin and Hippo pathways in mammary tumors, which was more evident at the protein rather than the mRNA level. Wnt/β-catenin and Hippo pathways seem to be involved in mammary carcinogenesis and therefore represent interesting therapeutic targets that should be further investigated.